Golden Age: The Urgency of Developmental Counseling and the Collaborative Role of Parents and Counselors - Rahmawana; Hamzanwadi (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
The Golden Age is a crucial period in a child's development, as it is the time of rapid growth and the formation of the foundations of personality. This article examines the importance of developmental counseling services as an approach that supports the overall growth and development of children from an early age. It also discusses the collaborative role of parents and counselors in creating a harmonious environment responsive to children's developmental needs. Drawing on theoretical support from figures such as Santrock and Bronfenbrenner, this article emphasizes that the active involvement of both parties is crucial to the success of the child support process. With effective synergy, children's potential can be optimally developed, and potential problems can be effectively addressed early